Sabzian : Sabzian is a collection of online reflections on cinema and maps cinephile events in Belgium and surroundings : #3. - Claes, Gerard-Jan; Grootaers, Elias ([S.l.] : Sabzian, 2016)
Over Kenji Mizoguchi ; Een lint van dromen ; Een fetisjistische camera. Over de films van Chantal Akerman ; Het vijfentwintigste scherm
boek